Evaluation of trends in hospital antimicrobial use in the Lao PDR using repeated point-prevalence surveys-evidence to improve treatment guideline use - Vilada Chansamouth; Danoy Chommanam; Tamalee Roberts; Sommay Keomany; Viladeth Paphasiri; Chanthala Phamisith; Siho Sengsavang; Khamsay Detleuxay; Phisith Phoutsavath; Sengvong Bouthavong; Anousone Douangnouvong; Manivanh Vongsouvath; et al. (Elsevier, 2022)
Summary: Background: Antimicrobial use (AMU) is a key driver of antimicrobial resistance (AMR). There are few data on AMU, to inform optimizing antibiotic stewardship, in the Lao PDR (Laos). Methods: Point prevalence surveys (PPS) of AMU were conducted at four-month intervals in six general hospitals across Laos from 2017 to 2020, using modified Global-PPS data collection tools. The surveys focused on AMU amongst hospitalized inpatients. Findings: The overall prevalence of inpatient AMU was 71% (4,377/6,188), varying by hospital and survey round from 50·4% (135/268) to 88·4% (61/69). Of 4,377 patients, 44% received >one antimicrobial. The total number of prescriptions assessed was 6,555. Ceftriaxone was the most commonly used (39·6%) antimicrobial, followed by metronidazole (17%) and gentamicin (10%). Pneumonia was the most common diagnosis among those prescribed antimicrobials in both children aged ≤5 years (29% among aged ≤1 year and 27% among aged >1 to ≤5years) and adults aged ≥15 years at 9%. The percentage of antimicrobial use compliant with local treatment guidelines was 26%; inappropriate use was mainly found for surgical prophylaxis (99%). Adult patients received ACCESS group antimicrobials less commonly than children (47% vs 63%, p-value<0·0001). Most WATCH group prescriptions (99%) were without a microbiological indication. Interpretation: AMU among hospitalized patients in Laos is high with frequent inappropriate use of antimicrobials, especially as surgical prophylaxis. Continued monitoring and enhanced antimicrobial stewardship interventions are needed in Lao hospitals. Funding: The Wellcome Trust [Grant numbers 220211/Z/20/Z and 214207/Z/18/Z] and bioMérieux.